2019
DOI: 10.1007/s00702-019-02074-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyposmia as a marker of (non-)motor disease severity in Parkinson’s disease

Abstract: The aim of this study was to evaluate the relationship of hyposmia in Parkinson’s disease (PD) with other motor and non-motor symptoms and with the degree of nigrostriatal dopaminergic cell loss. A total of 295 patients with a diagnosis of PD were included. Olfactory function was measured using the University of Pennsylvania Smell Identification Test (UPSIT). Motor symptoms were rated using the Unified Parkinson’s Disease Rating Scale motor subscale (UPDRS III). To evaluate other non-motor symptoms, we used th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 51 publications
6
35
1
Order By: Relevance
“…In addition, studies have also shown that patients with PIGD subtype have more deposition of α-synuclein and Aβ in the brain [ 19 ], which may also contribute to the faster disease progression and serious sleep disturbance. The HADS scores for anxiety and depression in PD patients with sleep disturbance were significantly higher than in PD patients without sleep disturbance, indicating that anxiety and depression are important factors affecting sleep status in PD patients [ 20 ]that are affected by the sleep quality [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have also shown that patients with PIGD subtype have more deposition of α-synuclein and Aβ in the brain [ 19 ], which may also contribute to the faster disease progression and serious sleep disturbance. The HADS scores for anxiety and depression in PD patients with sleep disturbance were significantly higher than in PD patients without sleep disturbance, indicating that anxiety and depression are important factors affecting sleep status in PD patients [ 20 ]that are affected by the sleep quality [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…OD has significant, moderate to strong associations with nigrostriatal degeneration (105,130,131). In one study, 98.7% of PD subjects with imaging evidence of nigrostriatal dopaminergic denervation had OD (130).…”
Section: How Is Od Related To Disease Onset and Progression?mentioning
confidence: 99%
“…To determine whether mice exhibited hyposmia, a promising marker for PD severity (Roos et al, 2019), mice were tested on the buried treat test (Dranka et al, 2014). Three days prior to testing, mice were habituated to fruit-scented cereal treats.…”
Section: Buried Treat Testmentioning
confidence: 99%